Dinamika Pembagian Waris Kepada Anak Hasil Perkawinan Beda Agama Menurut Hukum Perdata dan Hukum Islam di Indonesia - Roulina, Elisabeth Julietha; Gunawan, Clarissa; Sashenka, Kendrapatya Grisha; Alfarisi, Rafi; Tarina, Dwi Desi Yayi (Media Hukum Indonesia (MHI), 2025)
Marriages between religions cause separate problems because in this regard marriage not only has a personal relationship to the married couple, but it is also a denial of the legal issues living in Indonesia, as well as the sharing of child heirs with a married couple.